2019
DOI: 10.1186/s12890-019-0811-0
|View full text |Cite
|
Sign up to set email alerts
|

Limited overlap in significant hits between genome-wide association studies on two airflow obstruction definitions in the same population

Abstract: Background Airflow obstruction is a hallmark of chronic obstructive pulmonary disease (COPD), and is defined as either the ratio between forced expiratory volume in one second and forced vital capacity (FEV 1 /FVC) < 70% or < lower limit of normal (LLN). This study aimed to assess the overlap between genome-wide association studies (GWAS) on airflow obstruction using these two definitions in the same population stratified by smoking. Methods G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, the observation that GRS-structure associations were independent of lung function could be consistent with lung structure indexing "preobstructive" disease (16,17) and/or nonobstructive emphysema or the "symptomatic smoking" phenotype (14,35,59). Future studies should examine causal pathways more precisely by leveraging structurespecific GWAS signals, subclassified COPD endotypes, and longitudinal measurements of disease incidence and progression (60,61).…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the observation that GRS-structure associations were independent of lung function could be consistent with lung structure indexing "preobstructive" disease (16,17) and/or nonobstructive emphysema or the "symptomatic smoking" phenotype (14,35,59). Future studies should examine causal pathways more precisely by leveraging structurespecific GWAS signals, subclassified COPD endotypes, and longitudinal measurements of disease incidence and progression (60,61).…”
Section: Discussionmentioning
confidence: 81%
“…There have been few studies regarding the function of NFYC-AS1. For instance, van der Plaat et al found that NFYC-AS1 may play a role in airflow obstruction in never smokers by analyzing the genome-wide association study (GWAS) data (15). However, the authors also did not further verify the function of NFYC-AS1 in cell lines or animal models.…”
Section: Introductionmentioning
confidence: 99%
“…We defined two phenotypes when assessing chronic respiratory disease: airflow obstruction and asthma. Airflow obstruction, assessed by pre-bronchodilator spirometry (measured using a Welch Allyn Version 1.6.0.489, PC-based SpiroPerfect with Ca Workstation software), was defined as a ratio between the forced expiratory volume in one second and the forced vital capacity (FEV 1 /FVC) below the lower limit of normal (LLN) [ 25 ]. The LLN reference value was based on age, gender, height and ethnicity, and was calculated as the lower fifth percentile of a healthy reference population [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Airflow obstruction, assessed by pre-bronchodilator spirometry (measured using a Welch Allyn Version 1.6.0.489, PC-based SpiroPerfect with Ca Workstation software), was defined as a ratio between the forced expiratory volume in one second and the forced vital capacity (FEV 1 /FVC) below the lower limit of normal (LLN) [ 25 ]. The LLN reference value was based on age, gender, height and ethnicity, and was calculated as the lower fifth percentile of a healthy reference population [ 25 , 26 ]. Asthma was considered present if either a doctor had made the diagnosis or the patient used asthma medication and reported two or more symptoms from among wheeze, dyspnea at rest, and wakened by dyspnea.…”
Section: Methodsmentioning
confidence: 99%